Pengembangan Model Pembelajaran Diskusi dan Personal Investigation dalam Meningkatkan Pemahaman Mahasiswa pada Mata Kuliah Evaluasi Pembelajaran di Universitas Batanghari - Pratiwi Indah Sari; Kartika Dewi; Fitri Ayuningsih (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Errors in this learning process also occur in tertiary education. Some lecturers sometimes only focus on providing material with the aim of pursuing material achievement, so they don't think about how students understand it. This should not happen again in education, especially higher education, where students have been able to develop their own knowledge given. At the tertiary level, students must be able to develop what is in them. Students should be able to obtain information, solve problems that occur in learning. Based on the results of data analysis that have been obtained previously, there is a difference between the use of the lecture method with the discussion learning model and personal investigation on students of the Economic Education Study Program and the English Education Study Program, the Teacher Training and Education Faculty, Batanghari University in the Learning Evaluation course. This means that the application of new teaching methods can certainly have an impact and change even without eliminating the meaning of the learning itself. Thus, the application of the learning model is not only to attract students' interest and attention to the provision of lecture material, but to familiarize themselves so that they want to develop themselves in receiving information so that in the end it will improve their learning outcomes. This is because students are the final level in a learning process which is expected not only to have good character and personality, but also to have insight and knowledge globally as well.